Isotopic discrimination in helminths infecting coral reef fishes depends on parasite group, habitat within host, and host stable isotope value - Philip M. Riekenberg (Nature Portfolio, 2021)
Abstract Stable isotopes of carbon and nitrogen characterize trophic relationships in predator–prey relationships, with clear differences between consumer and diet (discrimination factor Δ13C and Δ15N). However, parasite–host isotopic relationships remain unclear, with Δ13C and Δ15N remaining incompletely characterized, especially for helminths. In this study, we used stable isotopes to determine discrimination factors for 13 parasite–host pairings of helminths in coral reef fish. Differences in Δ15N values grouped according to parasite groups and habitat within the host with positive Δ15N values observed for trematodes and nematodes from the digestive tract and variable Δ15N values observed for cestodes and nematodes from the general cavity. Furthermore, Δ13C values showed more complex patterns with no effect of parasite group or habitat within host. A negative relationship was observed between Δ15N and host δ15N values among different host-parasite pairings as well as within 7 out of the 13 pairings, indicating that host metabolic processing affects host-parasite discrimination values. In contrast, no relationships were observed for Δ13C values. Our results indicate that parasite group, habitat within host, and host stable isotope value drive Δ15N of helminths in coral reef fish while their effect on Δ13C is more idiosyncratic. These results call for use of taxon- or species-specific and scaled framework for bulk stable isotopes in the trophic ecology of parasites.